البنية السردية في رواية إدلب لورده عي - بوقرة, شابي, سهام أمال (Univercty of Eloued, 2020)
تعد هذه الدارسة ضمن الدارسات الحديثة للرواية والتي تبحث في عمق دارسة البنية السردية الزمان المكان الشخصية-في الرواية الجازئرية من خلال رواية ادلب، والتي برزت من خلال النسيج السردي فقد أبدعت الروائية في إنجازه، مجسدا في الشخوص بكلThis study is considered among the recent studies of the novel, which searches in the depth of the study of the narrative structure of time, place, personal - in the Algerian novel through the novel of IDLIB, which emerged through the narrative fabric, as the novelist excelled in its achievement, embodying the characters in all their religious, literary and physical dimensions ...
Keywords: البينة السردية- الشخصية; The novel - the narrative evidence - the personal.